Factors that influence economic growth in Vietnam / Nur Syuhada Rosli - Rosli, Nur Syuhada (2022)
Economic growth has been identified as one of the Vietnamese government's top priorities in recent years. This study aims to identify the factors that influence economic growth in Vietnam over the period of 1997 to 2020 and used annual time series data from Vietnam over a 24-year period. Particularly in emerging countries, economic growth is the most powerful tool for eliminating poverty and enhancing quality of life. Economic growth is a measure of a country's development performance and it is influenced by a variety of factors. This is due to the fact that various factors influence the country's economic growth. Furthermore, this study used five independent variables namely foreign direct investment, inflation, exports, gross domestic investment and corruption perception index which become the reasons of bringing change in economic growth of the country. Gross domestic product has been used as a proxy for the country's economic growth as the dependent variable in this study. Moreover, the Ordinary Least Squares (OLS) regression method was used in this paper to determine the significance of the independent variables in influencing economic growth. The correlation test, heteroscedasticity test and multicollinearity test were also employed in this study. Therefore, the main objective of this paper is to identify the relationship between GDP and its independent variables (FDI, INF, EXP, GDI and CPI) using annual data starting from 1997 to 2020. Overall, the findings show that all of the independent variables had a statistically insignificant relationship with economic growth in Vietnam over the study period. In other words, the independent factors have no effect on Vietnam's economic growth.